Three Models of Vaccination Strategies Against Cryptococcosis in Immunocompromised Hosts Using Heat-Killed Cryptococcus neoformans Δsgl1 - Normile, Tyler G.; Del Poeta, Maurizio (Frontiers in Immunology, 2022)
Vaccines are one of the greatest medical accomplishments to date, yet no fungal vaccines are currently available in humans mainly because opportunistic mycoses generally occur during immunodeficiencies necessary for vaccine protection. In previous studies, a live, attenuated Cryptococcus neoformans sgl1 mutant accumulating sterylglucosides was found to be avirulent and protected mice from a subsequent lethal infection even in absence of CD4+ T cells, a condition most associated with cryptococcosis (e.g., HIV). Here, we tested three strategies of vaccination against cryptococcosis. First, in our preventative model, protection was achieved even after a 3-fold increase of the vaccination window. Second, because live C. neoformans sgl1-vaccinated mice challenged more than once with WT strain had a significant decrease in lung fungal burden, we tested C. neoformans sgl1 as an immunotherapeutic. We found that therapeutic administrations of HK C. neoformans sgl1 post WT challenge significantly improves the lung fungal burden. Similarly, therapeutic administration of HK C. neoformans sgl1 post WT challenge resulted in 100% or 70% survival depending on the time of vaccine administration, suggesting that HK sgl1 is a robust immunotherapeutic option. Third, we investigated a novel model of vaccination in preventing reactivation from lung granuloma using C. neoformans gcs1. Remarkably, we show that administration of HK sgl1 prevents mice from reactivating gcs1 upon inducing immunosuppression with corticosteroids or by depleting CD4+ T cells. Our results suggest that HK sgl1 represents a clinically relevant, efficacious vaccine that confers robust host protection in three models of vaccination against cryptococcosis even during CD4-deficiency.